Pengaruh Pemberian Cincau Hitam Terhadap Penurunan Tekanan Darah Sistolik Pada Penderita Hipertensi Grade I di Desa Maneron Kecamatan Sepulu Kabupaten Bangkalan - Jayadi, Alpian; Jannah, Kholifatul (Sekolah Tinggi Ilmu Kesehatan Surabaya, 2017)
Hypertension grade 1 is problem that many people experienced in Maneron Village. Hypertension grade 1 is caused by Age factor, and poor diet. The purpose of this study to determine the effect of grass jelly giving on the decrease in systolic blood pressure in patients with grade 1 hypertension.          This type of research is an Quasi experimental design attempts to reveal causal relationships by involving control groups in addition to the experimental group. 22 respondents taken only 20 samples with purposive sampling technique, which is divided into two groups where 10 as the treatment group and 10 as the control group.        The results showed that the decrease in blood pressure in hypertensive patients was very significant, because after administering black grass for 1 week morning and night on a regular basis based on the test wilxocon ρ (0,010) <0,05. The value of α (0.05) which means H1 is received so that there is an effect of black grass giving on the decrease in systolic blood pressure in patients with Grade I hypertension in Maneron Village, Sepulu Subdistrict, Bangkalan District. This is evident from the results of research on the decrease in blood pressure after being given a black jellyfish drink. The conclusion of this research is expected this thesis can add references and provide knowledge that can utilize other non-pharmacological drug administration method related to arterosklerosis disease, diabetes militus, gout, rheumatism.